Fiscal deficit forecasts in Europe: Evidence for a double standard? - Jakub Rybacki (Baltic Journal of Economics, 2021)
Fiscal forecasts produced by international institutions came under strong criticism after the Eurozone sovereign debt crisis due to excessive optimism. Presently, international organizations are also accused of applying a double standard. Their opponents claim they depict negative picture for populist governments. This paper evaluates forecasts provided by the IMF, European Commission and the OECD based on a panel of EU economies and selected large countries. Five years after the Sovereign debt crisis, we still find excessively optimistic forecasts for Portugal and Spain. Moreover, the EC and OECD are being indulgent to countries under the excessive deficit procedure. There is also a strong autocorrelation of forecast errors and cyclical biases - European Commission overestimates governments' propensity to tighten fiscal policy during expansion and forecasts an overly pessimistic picture during a slowdown. However, we find no evidence suggesting that fiscal forecasts stigmatize the governments accused of populism.
Keywords: 62; 68; 330; Deficit forecasts; Excessive deficit procedure; Fiscal supervision; Public finance